2020
DOI: 10.7150/jca.40186
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Latency-Associated Transcripts (LATs) of Herpes Simplex Viruses

Abstract: Herpes simplex viruses (HSVs) cause cold sores and genital herpes and can establish lifelong latent infection in neurons. An engineered oncolytic HSV (oHSV) has recently been approved to treat tumors in clinics. HSV latency-associated transcripts (LATs) are associated with the latent infection, but LAT transcriptional regulation was seldom reported. For a better treatment of HSV infection and tumors, here we sequenced the LAT encoding DNA and LAT transcription regulatory region of our recently isolated new str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 78 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…(b) A sufficient amount of IE gene expression can produce a large amount of ICP0 protein. ICP0 activates the JNK signaling pathway, and then AP-1 is phosphorylated by JNK and traffics into the neural nucleus, where AP-1 binds to the transcription regulatory sequence of LAT and activates LAT transcription as we reported recently, 10 leading to latent infection of HSV. At the same time, LAT transcription sequence is complementary to the IE gene encoding ICP0, which continuously consumes ICP0, resulting in the corresponding decrease in IE gene expression.…”
Section: The Three Pathways To Hsv Latent Infectionmentioning
confidence: 53%
See 1 more Smart Citation
“…(b) A sufficient amount of IE gene expression can produce a large amount of ICP0 protein. ICP0 activates the JNK signaling pathway, and then AP-1 is phosphorylated by JNK and traffics into the neural nucleus, where AP-1 binds to the transcription regulatory sequence of LAT and activates LAT transcription as we reported recently, 10 leading to latent infection of HSV. At the same time, LAT transcription sequence is complementary to the IE gene encoding ICP0, which continuously consumes ICP0, resulting in the corresponding decrease in IE gene expression.…”
Section: The Three Pathways To Hsv Latent Infectionmentioning
confidence: 53%
“… 8 , 9 Engineered oHSVs have been reported in many clinical trials. 10 T-VEC is an engineered oHSV with deletion of the genes ICP34.5 and ICP47 and insertion of the gene encoding human GM-CSF. 11 In 2015, T-VEC was approved to treat the advanced melanoma in US.…”
Section: Introductionmentioning
confidence: 99%
“…Humans infected with HSV-1 may produce a series of skin lesions and neurotoxicity. Subsequently, HSV-1 establishes latency infection in the nervous system [11]. HSV-1 can be latent for several years or even a lifetime [12].…”
Section: Structure and Function Of Icp345 And Latmentioning
confidence: 99%
“…Perng G et al [31] reported the deletion of HSV-1 LAT genes. The absence of LAT and ICP34.5 prevents the virus from latency and reactivation, which means there has a long-term safe margin after treatment [11]. Therefore, LAT and ICP34.5 engineering are essential for the construction of oHSV.…”
Section: Oncolytic Engineering Of Icp345 and Lat Of Hsvmentioning
confidence: 99%
“…Under the periodic stimulation of different stressors, the latent state of infected neurons is activated and then enters the lytic cycle to regenerate infectious virions (Kennedy et al, 2015;Whitley and Baines, 2018;Rübben, 2020). The establishment of latent infection is related to the interaction between the viral genome and the nuclear environment (Zhang et al, 2020). The viral genome and promyelocytic leukemia (PML) protein occupy the same nuclear region in infected neurons and eventually form nucleosome structures containing viral DNA (PML-NBs) (Cohen et al, 2018;Watson et al, 2018).…”
Section: De Novo Synthesis Of Vp16 Coordinates Reactivation From Hsv mentioning
confidence: 99%